Peningkatan Aktivitas dan Hasil Belajar IPA dengan Metode Problem Solving pada Materi Listrik Dinamis di SMP Negeri 9 Metro - Mujiyono Mujiyono (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
This research was conducted at the 9 Metro Middle School in Jalan Charter Jakarta 16P Metro West Metro City with research subjects of class IX of SMP Negeri 9 Metro. To obtain research data used test and observation techniques. The results of the research were in the form of student activities at each meeting and learning outcomes at the beginning and end of the cycle. The average percentage of student activity in learning activities in the first cycle was 61.17%, while in the second cycle it was 8.63%. The average percentage of learning outcomes in the first cycle is 6.464 and in the second cycle is 7.214, so the increase is 0.55. Student learning outcomes have reached the expected indicators, namely 92.5% of students get a value of ≥ 60. The results of research on class IX students of SMP Negeri 9 Metro odd semester show that learning with problem solving methods can improve student learning activities and outcomes. Therefore, it is recommended to teachers of physics courses so that problem solving methods can be used as an alternative in learning physics in schools, especially in SMP Negeri 9 Metro.